A Note on the Derivation of the Basic Needs Deficiency Index (BNDI) - Abdullah, Naziruddin; Al-Malkawi, Husam-Aldin N. (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2009)
This paper develops an improvised methodology to measure poverty reduction for various categories, namely countries, regions, sub-groups, just to name a few. To this end, first, using mathematical expositions an index known as Basic Needs Deficiency Index (BNDI) is formulated. Second, this paper shows how the index can be used in empirical works, which in many respects are more convenient than the ones developed by other researchers in this area. Finally, by ranking and classifying the index, the status of poverty of a country can easily be gauged and hence mitigated.